2004
DOI: 10.1016/s0022-3999(04)00445-3
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbances among HIV-positive adultsThe role of pain, stress, and social support

Abstract: As expected, pain was significantly associated with sleep disturbance. Additionally, psychosocial variables were strongly associated with sleep. The type of support from friends differentiated whether the support was positively or negatively associated with sleep problems. Social support, depending on the type, may not always be helpful for adults living with HIV/AIDS. Future studies need to examine factors that may mediate the relationship between psychosocial constructs and healthy sleep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 0 publications
2
37
1
2
Order By: Relevance
“…Approximately one third of the general population reports occasional sleep problems, and about 10% have chronic insomnia (Roth, 2005;Fullerton, 2006). Sleep difficulty is associated with high rates of physical illness, psychiatric disorders, accidents, health care service utilization, social network problems, and employment-related difficulties (Roth et al, 2006;Sateia & Pigeon, 2004;Ohayona & Roth, 2003;Tjepkema, 2005;Vosvick et al, 2004). Many people with sleep problems have a greater tendency to use both licit and illicit substances to attempt to improve sleep functioning (e.g., Crum, Ford, Storr & Chan, 2004;Johnson, Roehrs, Roth & Breslau, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately one third of the general population reports occasional sleep problems, and about 10% have chronic insomnia (Roth, 2005;Fullerton, 2006). Sleep difficulty is associated with high rates of physical illness, psychiatric disorders, accidents, health care service utilization, social network problems, and employment-related difficulties (Roth et al, 2006;Sateia & Pigeon, 2004;Ohayona & Roth, 2003;Tjepkema, 2005;Vosvick et al, 2004). Many people with sleep problems have a greater tendency to use both licit and illicit substances to attempt to improve sleep functioning (e.g., Crum, Ford, Storr & Chan, 2004;Johnson, Roehrs, Roth & Breslau, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The characterization of the 33 articles showed that the year of publication ranged 1994-2013, being published in 15 European countries, [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] in the United States, 1,24-37 two in Brazil [38][39] and one in Argentina. 40 As the evidence levels, 8 there was the following distribution: an article level II, 31 an article level IV 11 articles level VI.…”
Section: Resultsmentioning
confidence: 99%
“…40 As the evidence levels, 8 there was the following distribution: an article level II, 31 an article level IV 11 articles level VI. 1,[9][10][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][32][33][34][35][36][37][38][39][40] It was found that most of the findings were derived from cross-sectional and descriptive studies, occurring direct observation of a planned number of people with HIV/ AIDS in a lifetime opportunity, which prevents comparisons of long-term sample characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations